Modification of Lipid Profile in Commercial Cow Milk Samples before and after Their Expiration Date: Evaluation of Storage Crucial Parameters and Possible Environmentally Friendly Disposal Alternatives - Eduardo Sommella; Manuela Giovanna Basilicata; Gian Carlo Tenore; Michele Manfra; Raffaella Mastrocinque; Carmine Ostacolo; Andrea Vitale; Marcello Chieppa; Pietro Campiglia; Giacomo Pepe (Journal of Food Quality)
Milk waste is considered a highly polluting material and its disposal is an economic and environmental problem for the dairy sector. Despite this, it can be turned into a source of nutraceutical products and biodiesel substrate. The objective of this study was to determine the qualitative and quantitative variation of single fatty acids in cow milk samples before expiration date and within 28 days after expiration date in order to monitor how the profile of the lipid fraction is influenced by different physicochemical parameters. It was shown that lipolysis in milk is a process independent of time but dependent on the values of pH and total titratable acidity, while crucial parameters for the lipid oxidation are temperature and time of exposure to atmospheric oxygen. All of these factors are at the basis of the efficacy of milk storage conditions. Moreover, our data demonstrate that milk, several weeks after its expiry date, is a rich source of fatty acids that may be recovered as potential substrates for the formulation of economically viable products and eco-friendly diesel-like fuels.